Population pharmacokinetic modeling of missed mycophenolate mofetil doses: Impact on exposure and exploration of mitigation strategies - Franck Maizaud; Selim Arraki-Zava; Hamza Sayadi; Yeleen Fromage; Pierre Marquet; Jean-Baptiste Woillard; Caroline Monchaud (PLoS ONE, 2025)
Background Missed doses of mycophenolate mofetil (MMF) are frequent in transplant recipients and may lead to subtherapeutic exposure to mycophenolic acid (MPA), potentially compromising graft function. However, current guidance on how to manage such deviations remains empirical and is not supported by pharmacokinetic evidence. Methods We used two validated population pharmacokinetic models of MPA to simulate steady-state exposure in virtual cohorts of renal transplant recipients treated with MMF. Scenarios included full missed doses, delays in intake (2–10 hours), and compensation strategies (50% or 100% added at the next dose). Simulations were performed for six dose regimens (500–1250 mg BID) and analyzed in terms of AUC0–12h, proportion of patients outside the target range (30–60 mg·h/L), and time to return to steady state. Results A fully missed dose resulted in a 40–60% reduction in AUC0–12h, with delayed return to steady state (up to 72 hours). Delays ≤6 hours caused minimal impact (<15% reduction). Full-dose compensation frequently overshot the therapeutic window, especially in higher-dose regimens. In contrast, adding 50% of the missed dose restored exposure safely and rapidly. When exact compensation was not feasible, rounding down to the nearest available formulation minimized overexposure. Conclusions Model-based simulations suggest that a rational response to MMF dose omissions can mitigate underexposure while avoiding toxicity. These strategies may support clinicians in managing missed doses and optimizing immunosuppressive therapy in kidney transplant recipients.